Formulación del plan de manejo de residuos sólidos para el área urbana del distrito de Simbal, provincia de Trujillo - Goicochea Velezmoro, Arnold Alberto (2019)
The present research work was carried out in the district of Simbal due to the lack of environmental management related to solid waste. Based on the Guía Metodológica para el desarrollo del Plan de Manejo de Residuos Sólidos, we elaborated a work plan, starting with the collection of information through the use of surveys to the population and local businesses, working with a sample of 45 homes and 15 establishments, as well as requests addressed to the municipality. Subsequently, training was given to the municipality staff and the population, following with the characterization study, which obtained 0,458 kg/hab.d, 36,59% humidity and 122,560 kg/m3 density. With the data obtained, the guidelines and necessary actions were outlined in the short, medium and long term to improve solid waste management. By way of conclusion, it was observed that the per-capita generation is lower compared to the department of La Libertad (0,51 kg/hab.d) due to the difference in purchasing power and the predominant agricultural activity compared to other districts